Treatment of hemimasticatory spasm secondary to parry-romberg syndrome via partial resection of the trigeminal nerve motor branch under intraoperative neurophysiological monitoring: A case report and literature review - Xu, Haitong; Xu, Bin; Huang, Xianjian; Zhang, Doudou; Cai, Xiaodong (Frontiers in Surgery, 2023)
Parry-Romberg syndrome (PRS) combined with hemimasticatory spasm (HMS) is a rare craniofacial disorder characterized by unilateral facial tissue atrophy with paroxysmal involuntary contractions of the jaw-closing muscles. Although a majority believe that this is a result of demyelination changes from the effect of the facial involvement of PRS on the trigeminal nerve motor branches, the mechanism of PRS is presently unclear. Moreover, the therapeutic effects of existing drugs that target PRS have not been satisfactory. For intolerable spasms of the masticatory muscles, botulinum toxin injection may temporarily relieve the symptoms of spasms. We report a case of HMS secondary to PRS that was treated via a partial resection of the trigeminal nerve motor branch under intraoperative neurophysiological monitoring.